Health, safety and environmental study of glass bubble application drilling and completion fluids / Wang Ning - Wang, Ning (2018)
Lightweight drilling and completion fluids are widely used for near-balanced, balanced or under-balanced drilling to reduce loss of fluids which can cause serious problems. They are also used to protect the reservoirs during the drilling process. As a newly introduced technology, glass bubbles, also known as Hollow Glass Spheres (HGS), are now being used to obtain lightweight fluids instead of other technologies such as air/dust drilling, as they are more environmentally friendly and low-cost. The health, safety, and environmental impacts of the application of glass bubbles in drilling and completion fluids have been previously reviewed and studied. By doing literature review and analyzing the process of their application, two health, safety, and environmental risks were found: lung disease attributable to inhalation of glass bubble dust and physical injury resulting from direct contact with glass bubbles. To avoid such risks, several suggested measures have been proposed. Moreover, the environmental impact of the application of glass bubbles in drilling and completion fluids is quite unobvious, and so there is an opportunity and reason to conduct further investigation and research on this subject matter